Wide Row Planting In Sugarcane – New Vistas for Augmenting Cane Production - Keshavaiah, Kuppahalli Venkataramaiah; Devaraju, Kumbaradoddi M. (Asian Journal of Biological and Life Sciences, 2015)
An experiment conducted at Zonal agricultural research station, V.C.Farm, Mandya with wide row planting of 5 feet spacing in comparison with conventional 3 feet spacing and 20 per cent reduced seed rate with wide row spacing with five varieties of sugarcane has revealed that there exists statistically non significant difference in cane yield with wide row spacing (131.85 t ha-1 144.5 t ha-1 and respectively). The sugar percent was genetic in nature and Co 86032 exhibited higher sugar content and recorded higher sugar yield in both the spacings. Co 86032 (21.77 t ha-1) and Co62175 (20.46 t ha-1) have recorded higher sugar yield with wider spacing and lesser seed rate indicating the suitability for wide row planting of cane and Co 8371 is unsuitable for wide row planting of cane due to its poor tillering ability. As there is no reduction in cane yield to a significant level, wide row planting is useful due to many other advantages that accrue to wide row planting.
Keywords: reduced seed rate and varieties of sugarcane; wide row planting